Mapping of the Geological Structures Using Digital Elevation Model (DEM)-Derived Flow Direction: A Case Study of Rungwe Volcanic Province, Southwest Tanzania - Mshiu, Elisante Elisaimon (Tanzania Journal of Science, 2020)
This study aimed to assess the potentiality of Digital Elevation Model (DEM)-derived flow direction in mapping geologic structures, specifically in areas with thick overburden of soil or volcanic materials such as in the Rungwe Volcanic Province, SW Tanzania. Clustering of flow directions based on trends of structure sets found in the study area was applied and it successfully revealed a large number of geological structures through demarcated tectonic blocks from patterns created by flow directions. Northwest–southwest (NW-SE) and NE-SW- trending lineaments are the dominant structural sets in the area whereas N-S and E-W-trending lineaments constitute the minor sets. Moreover, the approach has also unveiled the NW-SE-trending faults that control most of the volcanic centers. The extracted lineaments by the method presented in this research are consistent with the known geological structures and structure surface manifestations such as volcanic centers, hot springs and earthquake epicenters. Findings of this study has revealed that the method can be applied as a robust technique to map crustal structures mostly in early phases of exploration, and has shown good results in delineating faults in areas with thick overburden such as soils and volcanic materials.